Middle East illusions including peace in the Middle East? : reflections on justice and nationhood - Chomsky, Noam (Palgrave Macmillan, 2003)
Discusses the history of the ongoing conflict between Israel and Palestine, the involvement of the United States in the peace process, and the changing face of terrorism in the twenty-first century.